2020
DOI: 10.1088/1361-6463/abc583
|View full text |Cite
|
Sign up to set email alerts
|

Actuation efficiency of nanosecond repetitively pulsed discharges for plasma-assisted swirl flames at pressures up to 3 bar

Abstract: This study analyzes different strategies of plasma actuation of premixed swirl flames at pressures up to 3 bar. A wide range of applied voltages and pulse repetition frequencies (PRF) is considered, resulting in different combinations of nanosecond repetitively pulsed (NRP) discharge regimes, NRP glow and NRP spark discharges. Electrical characterization of the discharges is performed, measuring voltage and current, and deposited energy and power are evaluated. The effectiveness of the plasma actuation is asse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 30 publications
1
16
0
Order By: Relevance
“…On the other hand, if the shock waves are too strong, they may destabilize the combustion. This was recently discussed in [180], where at pressures above 2 bar, it was found that spark NRPD (with strong gas heating and shock wave generation) were less efficient than glow NRPD (promoting a chemical effect), for flame anchoring. 6 Plasma-assisted detonation Detonation refers to a supersonic regime of combustion.…”
Section: Combined Thermal and Transport Effectsmentioning
confidence: 87%
See 2 more Smart Citations
“…On the other hand, if the shock waves are too strong, they may destabilize the combustion. This was recently discussed in [180], where at pressures above 2 bar, it was found that spark NRPD (with strong gas heating and shock wave generation) were less efficient than glow NRPD (promoting a chemical effect), for flame anchoring. 6 Plasma-assisted detonation Detonation refers to a supersonic regime of combustion.…”
Section: Combined Thermal and Transport Effectsmentioning
confidence: 87%
“…However, the effect of sub-breakdown electric fields on flames (e.g., [155][156][157][158][159]161]) is also commonly considered as a PAC process. The end goals of PAC studies can be grouped into three categories: (1) increase the flammability limits [47,112,[164][165][166]171], (2) stabilize the combustion [172][173][174][175][176][177]179,180], and (3) enhance the burning properties (e.g., burning velocity, soot or pollutant emis-sions. .…”
Section: Plasma-assisted Combustionmentioning
confidence: 99%
See 1 more Smart Citation
“…Overly strong distortion, however, could result in localized extinction -particularly at leaner mixtures. 51 Faster flame development should benefit PC ignition as a greater fraction of the fuel-air mixture was consumed within the PC volume before it can be pushed out through the nozzles due to pressure buildup. Moreover, the benefit should be more pronounced with larger internal PC volumes as the effect of wall quench became less pronounced.…”
Section: Isp and Nrp Discharge Characteristicsmentioning
confidence: 99%
“…An emerging solution to enable flame stabilization, suitable to a wide range of combustion applications, is to locally generate a plasma [2,3]. Among the various possible types of discharges to enhance combustion [4,5], the Nanosecond Repetitively Pulsed (NRP) discharges [6] succeeded to stabilize ultra-lean premixed flames on several laboratory-scale hydrocarbon-air flames [6,7] but also in test rigs representative of a gas turbine environment at atmospheric [8,9] and high pressure [10,11]. This technique is very efficient because the energy consumption of the plasma is typically less than 1% of the power released by the flame.…”
Section: Introductionmentioning
confidence: 99%